2012
DOI: 10.2478/v10207-012-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Fertilised Grassland Management Intensity on Herbage Quality and Quantity

Abstract: Effects of Non-Fertilised Grassland Management Intensity on Herbage Quality and Quantity Over 2006-2009, an optimum cutting frequency was investigated at non-fertilised grassland. The research was carried out at the Suchý vrch site (near Banská Bystrica), altitude 460 m. The research sward was utilised by cutting with different intensity: high (4 cuts), medium (3 cuts), low (2 cuts) and by 1 cut under extensive exploitation. Herbage yield, organic and mineral substances and nutritive value were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
0
1
1
Order By: Relevance
“…The same level of lower yield was then found on stands with temporarily reduced intensity of use (variants 7 and 8). In contrast to our results, Kováčiková et al (2012) found the highest production in stands mowed twice a year in an experiment with differentiated intensity of use.…”
Section: Resultscontrasting
confidence: 99%
“…The same level of lower yield was then found on stands with temporarily reduced intensity of use (variants 7 and 8). In contrast to our results, Kováčiková et al (2012) found the highest production in stands mowed twice a year in an experiment with differentiated intensity of use.…”
Section: Resultscontrasting
confidence: 99%
“…zrieďovací účinok, kedy so zvyšovaním úrod klesá obsah živín v sušine trávnych porastov. Nižší obsah dusíkatých látok v nadzemnej fytomase trávnych porastov hnojených minerálnymi hnojivami v porovnaní s nehnojenou kontrolou uvádzajú aj práce ďalších autorov (Hejcman et al, 2010;Jančovič et al, 2007;Frank, 2008;Kováčiková et al, 2013;Szewczyk et al, 2004).…”
Section: Materiál a Metódyunclassified